PENGARUH APLIKASI URIN SAPI SERTA JUMLAH RUAS TERHADAP PERTUMBUHAN STEK KOPI ROBUSTA (Coffea canepohora L.) - Cinantya, Devina; Rosdiana, Eva; Setyoko, Ujang; Nugroho, Setyo Andi; Fadillah, Anggita Rizky; Agustin, Ayu (JURNAL BIOSENSE, 2025)
The cultivation of Coffea canephora (robusta coffee) in Indonesia has undergone substantial growth in recent years. Propagation of robusta coffee can be achieved through both vegetative and generative methods; however, vegetative propagation via stem cuttings is the most widely adopted technique among coffee farmers. The success of stem cutting propagation is influenced by various factors, including the number of nodes per cutting and the application of growth-stimulating substances such as cow urine. This study aimed to assess the effects of cow urine concentration and the number of stem nodes on the growth performance of robusta coffee cuttings. A factorial experiment was conducted using a Randomized Complete Block Design (RCBD) with two factors. The first factor was cow urine concentration at three levels: 30% (U1), 45% (U2), and 60% (U3). The second factor was the number of nodes per cutting: 3 nodes (R1), 4 nodes (R2), and 5 nodes (R3), with each treatment combination replicated three times. The results demonstrated that the combination of 30% cow urine and four-node cuttings significantly enhanced the percentage of successful establishment. Moreover, the 30% cow urine treatment significantly improved shoot emergence rate, shoot length, and stem diameter. In contrast, the 60% concentration only showed a significant effect on leaf length.